The Influence Of E-Service Quality And E-Trust On The Purchase Decision Of Train Tickets On The Access By KAI Application - Asep Maulana; Riska Mayasta Putri (CV. Ulil Albab Corp, 2026)
This study aims to know, analyze and explain the effect of e-service quality and e-trust on the decision to purchase train tickets at Access by KAI. This study uses a quantitative method with descriptive and verifiable analysis. The population in this study is unknown and uses a simple random sampling approach.. The sample in the study amounted to 150 respondents. This study uses SPSS analysis tools. The results of this study show that e-service quality has a partial effect of 0.386 or 38.6% on purchase decisions and e-trust has a partial effect of 0.617 or 61.7% on purchase decisions. Then, e-service quality and e-trust had a simultaneous influence on purchase decisions of 0.808 or 80.8%, and 19.2% influenced by other variables.